Metabolic Syndrome Racial Differences in Adolescents - Hoffman, Robert P. (Current Diabetes Reviews, 2009)
The metabolic syndrome consists of obesity, insulin resistance, dyslipidemia, atherosclerosis, and hypertension. Its clinical outcomes are stroke, myocardial infarction, and type 2 diabetes. Each of these is more frequent in African- Americans than in Caucasians. This is surprising since most studies indicate that the incidence of the metabolic syndrome is lower in African-American than Caucasian adults. There is growing evidence that adult cardiovascular disease has its origin in childhood and adolescents. Thus, it is important that we understand differences in the pathophysiological precursors to metabolic and cardiovascular disease in this age group. Many studies, but not all, have demonstrated that African- American children and adolescents are insulin resistant compared to similar age Caucasians. The increased insulin resistance occurs in spite of lower triglyceride levels. Low triglyceride levels are usually associated with increased insulin sensitivity. There is evidence that the relationship between triglycerides and insulin sensitivity differs between the two races. African-Americans compensate for the increased insulin resistance by increasing insulin secretion and insulin clearance. Interestingly, those studies that have not found increased insulin resistance in African-Americans have found increased insulin secretion suggesting the increased secretion may precede the insulin resistance. Hyperinsulinism and insulin resistance are linked to endothelial dysfunction in adults and African-American adolescents have poorer endothelial function than do Caucasians. In African-American adolescents, endothelial function decreases as insulin secretion increases. It is likely that the hyperinsulinism, insulin resistance and endothelial dysfunction in adolescent African-American adolescents play an important role in the increased rates of cardiovascular disease and type 2 diabetes. Future research should focus on the mechanisms of these abnormalities and ways to prevent their development in this age group.